The Influence of Green Brand Positioning, Attitude, and Green Brand Knowledge on Purchase Intention of Mineral Botanica Products: (A Study on Consumers in Bandar Lampung) - Elvaretta, Devina; Roslina, Roslina (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to determine the effect of Green Brand Positioning, Attitude and Green Brand Knowledge on Consumer Purchase Intention towards Mineral Botanica products (Study on Consumers in Bandar Lampung City). The phenomenon of increasing public awareness of environmental issues encourages skincare manufacturers to implement desire-based marketing strategies. This study uses a quantitative approach with a survey method. The sample in this study was 200 respondents who were skincare consumers in Bandar Lampung, without age or generation restrictions. The sampling technique used purposive sampling, and data analysis was carried out using multiple linear regression using SPSS 25 software. The results showed that the variables Green Brand Positioning, Attitude and Green Brand Knowledge had a positive and significant effect on Purchase Intention. These findings indicate that brand placement that is oriented towards environmentally friendly values, positive consumer attitudes towards green brands, and good consumer knowledge about the brand can increase purchase intention towards Mineral Botanica products. This study is expected to be a strategic reference for skincare industry players in strengthening the image of sustainable brands in the local market.